Determination of the Conditional-Constant Component of the Bank’s Current Liabilities - Vozhzhov, Anatoly Pavlovich; Lunyakov, Oleg Vladimirovich; Lunyakova, Natalya Avtandilovna (Economy of Regions, 2016)
The article deals with the questions of the definition of the semi-constant component of current liabilities of a bank. The purpose of this article is to develop a scientific and methodological approach to determine the semi-constant component of the current liabilities of a bank under the conditions of the complexity of data acquisition and processing of the data on factors that influence on demand deposits. The main hypothesis is the assumption of the heterogeneity of the variance of the daily cumulative sum of demand deposits. The analysis of scientific and methodological approaches that allow determining a stable component of current liabilities proves the need for further improvement of scientific instruments. In particular, a coefficient analysis that is proposed by some of the scholars, mainly, considers the average values of turnover on accounts, which in turn, can vary considerably throughout the calendar year. The use of the probability distributions to determine the expected value of the constant sum of deposits is possible only in the case of “ideal" financial conditions, when the impact of factors on the aggregate sum of deposits is not taken into account. The developed statistical models leave out the possible heterogeneity of the dispersion of this balance. In the article, it is proposed to apply econometric methods, namely, the methods of time series analysis to test the hypothesis of the variance heterogeneity of the cumulative sum of demand deposits, using daily data. In particular, the formalization and evaluation of EGARCH-model parameters are conducted. The EGARCH-model allows to take into account the non-linear, asymmetric effects of fluctuations in the financial series. The determination of the conditional- constant component of demand deposits is proposed on the basis of the revealed regularities. The results of the research prove the hypothesis of the non-stationary character of the variance in daily balance of demand deposits. It may result from the economic shocks influence. The proposed scientific and methodological approach may be applied in the bank liabilities management both at the micro level and at the regional level of banking network.